A three‐dimensional mixed‐valence CuII/CuI coordination polymer constructed from biphenyl‐3, 4′, 5‐tricarboxylate and 1, 4‐bis(1H‐imidazol‐1‐yl)benzene ligands. Issue 4 (24th March 2016) - Liu, Ya-Hui; Lu, Li-Ping; Zhu, Miao-Li; Su, Feng
Abstract : A novel three‐dimensional Cu II /Cu I coordination polymer, with a (2, 2, 3, 4, 4)‐connected topological network, was assembled from biphenyl‐3, 4′, 5‐tricarboxylic acid and 1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene. An investigation of the magnetic properties indicated a very weak ferromagnetic behaviour. Abstract : Coordination polymers (CPs) built by coordination bonds between metal ions/clusters and multidentate organic ligands exhibit fascinating structural topologies and potential applications as functional solid materials. The title coordination polymer, poly[diaquabis(μ4 ‐biphenyl‐3, 4′, 5‐tricarboxylato‐κ 4 O 3 : O 3′ : O 4′ : O 5 )tris[μ2 ‐1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene‐κ 2 N 3 : N 3′ ]dicopper(II)dicopper(I)], [Cu II 2 Cu I 2 (C15 H7 O6 )2 (C12 H10 N4 )3 (H2 O)2 ] n, was crystallized from a mixture of biphenyl‐3, 4′, 5‐tricarboxylic acid (H3 bpt), 1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene (1, 4‐bib) and copper(II) chloride in a water–CH3 CN mixture under solvothermal reaction conditions. The asymmetric unit consists of two crystallographically independent Cu atoms, one of which is Cu II, while the other has been reduced to the Cu I ion. The Cu II centre is pentacoordinated by three O atoms from three bpt 3− ligands, one N atom from a 1, 4‐bib ligand and one O atom from a coordinated water molecule, and the coordination geometry can be described as distorted trigonal bipyramidal. The Cu I atom exhibits a T‐shaped geometry (CuN2 O) coordinated by one O atom from a bpt 3− ligand and two N atoms from two 1, 4‐bib ligands. The Cu II atoms are extended by bpt 3− and 1, 4‐bib linkers to generate a two‐dimensional network, while the Cu I atoms are linked by 1, 4‐bib ligands, forming one‐dimensional chains along the [20 ] direction. In addition, the completely deprotonated μ4 ‐η 1 :η 1 :η 1 :η 1 bpt 3− ligands bridge one Cu I and three Cu II cations along the a (or [100]) direction to form a three‐dimensional framework with a (10 3 )2 (10)2 (4 2 .6.10 2 .12)2 (4 2 .6.8 2 .10)2 (8) topology via a 2, 2, 3, 4, 4‐connected net. An investigation of the magnetic properties indicated a very weak ferromagnetic behaviour.